The Impact of Clinical Pharmacists on Improving Outcomes for Cancer Patients – A Systematic Review - Agnes Evonella Pangaribuan; Syafhan, Nadia Farhanah; Titiesari, Yovita Diane (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2026)
Background: Clinical pharmacists play a crucial role in the management and care of patients with cancer. Objective: This systematic review evaluated the effectiveness of clinical pharmacist-led interventions on clinical outcomes in patients with cancer undergoing chemotherapy. Methods: A comprehensive literature review was performed using PubMed, Scopus, and ScienceDirect, focusing on randomized controlled trials (RCTs) published between January 2010 and May 2025. The search included relevant keywords and MeSH terms such as “Antineoplastic Agents,” “Pharmaceutical Services,” and “Clinical pharmacists.” This study focused on English-language journals reporting on studies of patients with cancer undergoing chemotherapy, evaluating clinical pharmacist-led interventions. The initial search yielded 3,803 articles screened. After a thorough evaluation of the titles, abstracts, and full texts, along with an assessment of quality and risk of bias, 10 trials were included in the analysis.  Results: Clinical pharmacists help patients take their medications more effectively, improving patient adherence by up to 30%. They also reduce problems with side effects, adverse effects, and medication incompatibilities, with one study showing a 77.3% success rate in reducing problems with medications. Patient satisfaction was high at 93%, and quality of life improved. One study found cost savings of USD 269,420 over eight months of use. The intervention included messaging and vaccination programs for older adults, conducted in-person and online. Conclusion: Clinical pharmacist-led interventions are crucial for improving medication adherence, ensuring patient safety, and enhancing clinical outcomes in patients undergoing chemotherapy. Incorporating clinical pharmacists as integral members of the oncology care team is a valuable strategy.